Pengaruh Mekanisme Good Corporate Governance Terhadap Nilai Perusahaan dengan Manajemen Laba sebagai Variabel Intervening Pada Perusahaan Otomotif - Inta Hartaningtyas Rani; Lestari Adhi Widyowati; Jara Hardiyanti Jalih (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2020)
This study aims to examine the effect of good corporate governance mechanisms on earnings management, earnings management on value of the firm, good corporate governance mechanisms on value of the firm and whether the earnings management actions are intervening variables on the relationship between good corporate governance and value of the firm. Good corporate governance indicators used consists of managerial ownership, institutional ownership and audit committee. The population in this study are all automotive companies listed on the Indonesia Stock Exchange during 2015-2018. This study uses secondary data and purposive sampling methods. The analytical method used to test the hypotheses in this study is path analysis.